Sosialisasi Pengolahan Sampah Plastik Menjadi Paving Block di Bank Sampah Kelurahan Waru Kabupaten Penajam Paser Utara - Adi Prautomo; Ales Maulana; Febrian Dwi Arianto Putra Nave (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
The purpose of this community service activity is to increase the capacity of the management of the RT 28 Waste Bank in Waru Village, North Penajam Paser Regency, in managing plastic waste that was previously only collected and sold, and has not been utilized as a value-added product. This program is designed to address the problem of low innovation in plastic waste processing and the continued practice of burning waste in the community. The community service method uses a participatory approach through the stages of initial survey, planning, socialization, training, and evaluation. The survey was conducted to identify the condition of waste management. The equipment used includes plastic shredders, heating tools, paving block molds, and work safety equipment. The results of the community service activity include education on the impact of plastic waste, sorting and shredding practices, melting plastic, mixing with sand and used oil, to molding and cooling paving block products. Evaluation was carried out on the participants' understanding and the quality of the resulting products. The implications of the activity show an increase in the management's knowledge and skills in processing plastic waste productively. This program has the potential to reduce waste volume while opening up recycling-based business opportunities at the community level.